Педагогічна культура викладача вищої школи як ресурс підвищення якості освіти - Пономарьов, Олександр Семенович; Згурська, Марія Павлівна (НТУ "ХПІ", 2011)
The paper shows that the quality of Ukrainian higher education can be provided in such an important factor in improving the pedagogical culture of teachers. The direct relationship between the quality of graduate training and the level of the pedagogical culture of teachers.
Keywords: педагогічна культура; професійно-педагогічна майстерність; системний підхід; вища технічна освіта; управління якістю освіти; гуманітаризація освіти